Gambaran Pola Makan pada Balita dengan Stunting di Wilayah Kerja UPTD Puskesmas Mannanti Kecamatan Tellulimpoe Kabupaten Sinjai - Suryaningsi Ningsi; Fanny Dewi Sartika; Nurhijrani Nurhijrani; Khumaidi Arief (Fatiakara Care: Jurnal Ilmiah Keperawatan, 2026)
A healthy diet is a way of regulating the quantity and type of food with the aim of maintaining health, nutritional status, preventing, or assisting someone in relation to daily eating habits. Nutritional problems can arise if an individual's daily consumption does not meet their daily needs. One of the impacts of nutritional problems is the occurrence of stunting. Stunting (dwarfism) is a condition where toddlers have a height or length that is less than what is expected for their age. From the researchers' observations, it was found that there is still a lack of knowledge among mothers regarding proper feeding patterns for toddlers in the working area of UPTD Mannanti health center, Tellulimpoe district, Sinjai regency. Objective: The study aims to understand the dietary patterns of toddlers with stunting in the working area of of the the UPTD Mannanti health center, Tellulimpoe district, Sinjai regency. Method: This study uses a descriptive quantitative research method with a "cross-sectional" approach. The population in this study consists of 109 stunted toddlers, with a sample of 53 respondents, conducted from May to June 2025. Results: From 53 toddlers, 14 respondents (26.4%) had a good diet, 35 respondents (66.0%) had a sufficient diet, and 4 respondents (7.5%) had a poor diet. Conclusion: Based on the research conducted, it can be concluded that the average diet categorized as sufficient was the most prevalent in the working area of the UPTD Mannanti health center. Suggestion: With this research, it is hoped that it can help and remind parents of toddlers to pay attention to good dietary consumption for toddlers in order to support their growth and development.